Analysis Factors Related to Menstrual Disorders in Female Medical Students - Situmorang, Risna Sari; Desmawati, Desmawati; Murni, Arina Widya (Poltekkes Kemenkes Surakarta, 2025)
Background: Every woman can experience various disorders of menstruation, ranging from amenorrhea, oligomenorrhea, polymenorrhoea, hypomenorrhea, hypermenorrhoea, and dysmenorrhoea. This study aimed to elucidate the factors related to menstrual disorders in female students of the faculty of medicine at Universitas Andalas. Methods: The purpose of this case-control study is to determine factors that increase the likelihood of developing a disease by comparing a group of cases with a group of controls, focusing on their exposure status. The respondents to this study were teenagers aged 18-21 years. A sample of 108 female students was taken using consecutive sampling. Data collection from anthropometric measurements and questionnaires menarche age, The International Physical Activity Questionnaire (IPAQ), Food Frequencies Questionnaire (FFQ) and Pittsburg Sleep Quality Index (PSQI). The Chi-Square test was used to analyze the data. Results: The result showed no significant relationship between menarche age (p-value 0.420), stress levels (p-value 0.406), and physical activity (p-value 0.348), with menstrual disorders. There was a relationship between nutritional status (p-value 0.001), sleep quality (p-value 0.002), and eating patterns (p-value 0.001) with menstrual disorders. Conclusion: Diet is the factor most associated with menstrual disorders in female students, followed by sleep quality and nutritional status. The study recommends preventing menstrual disorders in female students by prioritising improvements in diet, sleep quality and nutritional status.